Produção e Reprodução de Bovina de Uma Fazenda no Mato Grosso do Sul. - Guilherme, Gabriel Oliveira (Universidade Federal do Tocantins, 2023)
This report presents the activities developed during the compulsory supervised curricular internship held from February 2 to May 31, 2019, totaling 820 hours. The internship was held at BRPEC Agropecuária, Fazenda Cristo Redentor. Located in the municipality of Miranda, Mato Grosso do Sul. Among the various activities carried out during the training stage, activities involving the use of reproductive biotechniques, company management and animal breeding were highlighted. The development of these activities enabled the trainee to develop a critical and professional sense of how these actions can contribute to the efficient performance of an agricultural system, since the farm works with agriculture and livestock and is its benchmark in short cycle livestock farming in Brazil and region of the Nhecolandia wetland. The development of internships in regions and areas that run away from their routine / knowledge becomes extremely important, since it allows several opportunities and maturity in the professional performance.